Developing a model for prediction of helical turbine flowmeter performance using CFD. (April 2015) - Saboohi, Zoheir; Sorkhkhah, Shahrokh; Shakeri, Hossein
Abstract: In this article, a numerical model for prediction of turbine flowmeter performance is proposed. This model is consists of a novel iterative algorithm, based on torque balance theory. Despite previous studies, the effect of bearings drag torque on finding balance point is considered. Using an in-house code, the bearings torque of the flowmeter is calculated based on the finite difference method. The three-dimensional steady state internal flow field of turbine flowmeter is obtained from the Computational Fluid Dynamics (CFD) simulations. For evaluation of the model׳s accuracy the experiments on a 6 in. helical turbine flowmeter has been carried out for crude oil and water. Consequently, the K-factor and also linearity error for cases of fluids are achieved. The results were compared with experimental data and it is found that the numerical model results are reasonably accurate. Therefore, by using the proposed model, the heavy cost of design and optimization of turbine flowmeters can be reduced. Highlights: A novel algorithm presented for predicting the performance of turbine flowmeters. Developed model is based on torque balance equation and considered the bearings drag torques. The model is applied to target helical turbine flowmeter at different flow rates of crude oil and water fluids. The results are compared to experimental measurements. By considering bearings drag torque simulative results improved and got closer to experimental data.